PENGARUH MEDIA SOSIAL INSTAGRAM DALAM MENINGKATKAN LITERASI DIGITAL WARGA NEGARA PADA MAHASISWA PPKN FKIP UNTIRTA - Apriani, Neni; Fitrayadi, Dinar Sugiana; Untari, Aryanti Dwi (UNTIRTA CIVIC EDUCATION JOURNAL, 2023)
The research aims to explore the impact of the social media platform Instagram in improving digital literacy skills among PPKn FKIP Untirta students. The research on PPKn FKIP Untirta students. The method applied is a survey that uses a quantitative approach. The population that is the focus of this research is active PPKn Untirta students who are registered from the 2021 to 2024 class. The sampling technique applied is probability sampling using the simple random sampling method. Findings from the research show that moderate Instagram use covers 85% of the total participants, totaling 64 people. Meanwhile, residents' digital literacy skills were categorized as moderate with a percentage of 80%, out of 60 participants. The level of influence can be seen from the significance value which shows 0.001 which is smaller than 0.05. Apart from that, the calculated t value was recorded as 5.208 which is greater than t table which has a value of 1.666, so it can be concluded that the variable (X) use of Instagram social media has an impact on the variable (Y) digital literacy of citizens. Thus, it can be concluded that there is a connection between Instagram Social Media and Citizen Digital Literacy among PPKn FKIP Untirta students.